The Comparison between Realia and Discovery Learning Techniques to Improve Students’ Vocabulary in Reading Comprehension - Khusnul Zakiah; Rosnani Sahardin (Research in English and Education Journal, 2022)
This study aimed to investigate the comparison between the use of Realia and Discovery Learning Techniques in improving the junior high school students’ vocabulary in reading comprehension. The sample was the second grade students of SMPN BUNGA BANGSA Nagan Raya consisting of 60 students from class VIII-1 and VIII-2. The research design used in this study is an experimental one in which there were two classes designed, one class used Realia and the other used Discovery Learning technique. The data were obtained from a pre-test and a post-test given to the students. The findings show that by using Realia technique, the mean score of the pre-test for vocabulary is 23.89 %and the mean score of the post-test is 72.22%. In addition, the mean score of the pre-test for comprehension is 21.67% and the post-test is 71.14%. While by using Discovery Learning, the mean score of pre-test for vocabulary is 24.46% and the post-test is 67.84%. Whereas, for the comprehension, the mean score of the pre-test is 20.28% and the post-test is 68.06%. Therefore, based on the complication, there is significant difference in reading comprehension score of students before given treatment using Realia and Discovery Learning techniques and after treatment. Thus, it can be said that Realia and Discovery Learning techniques improved students’ in reading comprehension and hence Ha is accepted because  after given treatment by Realia and Discovery Learning techniques, the students had better achievement in reading comprehension.